Enhancing the degradation of Aflatoxin B1 by co-cultivation of two fungi strains with the improved production of detoxifying enzymes. (1st March 2022) - Wang, Le; Huang, Wei; Shen, Yan; Zhao, Yawei; Wu, Dapeng; Yin, Haicheng; Yang, Shuoye; Yuan, Qipeng; Liang, Wenhui; Wang, Jinshui
Highlights: Developed mixed fungal cultures to produce enzymes for degradation AFB1 efficiently. The molecular weight ranges of the detoxifying enzymes were determined. The co-culture enhanced the enzymes production in the range of 58 kDa and 63 kDa. Eight degradation products from AFB1 were identified by LC-MS. Two degradation pathways for AFB1 were speculated in our research. Abstract: After the co-culture of Aspergillus niger and Pleurotus ostreatus, the obtained extracellular crude enzymes solution was employed to aflatoxin B1 (AFB1 ) degradation. The maximum AFB1 degradation with co-culture reached 93.4%, which increased by 65.9% and 37.6%, respectively, compared with those of the mono-culture of Pleurotus ostreatus and Aspergillus niger . The molecular weight of the key detoxifying enzymes isolated by ultrafiltration was 58 and 63 kDa by SDS-PAGE analysis. The purified detoxifying enzymes had a high detoxification effect on AFB1 with the degradation rate of 94.7%. It was found that the co-culture of Pleurotus ostreatus and Aspergillus niger promoted the production of 58 and 63 kDa detoxifying enzymes to enhance the AFB1 degradation. The chemical structure of major degradation products of AFB1 by the mixed cultures were preliminarily identified by LC-Triple TOF MS. Two pathways of AFB1 degradation were inferred with the high potential of fungal co-cultivations for AFB1 detoxification applications.